Evaluation of Anxiety and Depression Scores in Patients Receiving Radiotherapy During First Wave of COVID-19 Pandemic - Dağdelen, Meltem; Demir, Ecem; Ergen, Arzu; Demirel, Ömer Faruk; Yıldırım, Cumhur; Uzel, Ömer E.; Şahinler, İsmet; Öner Dinçbaş, H. Fazilet; Çolpan Öksüz, Didem (Cerrahpaşa Medical Journal, 2022)
Objective: The aim of this study was to assess the anxiety and depression levels of cancer patients who were treated with radiotherapy during the coronavirus disease-2019 pandemic. Methods: Between April and June 2020, 66 patients were included in the study. The Hospital Anxiety and Depression test was applied in order to determine patients’ anxiety and depression levels. Patients filled out the questionnaire before the first day of irradiation. Results: The rates of anxiety and depression in our study were 53% and 59%, respectively. The mean score of Hospital Anxiety and Depression Scale-Anxiety among women (10.8 ± 3) was above the Turkish population cut-off level of 10. The mean Hospital Anxiety and Depression Scale-Anxiety score among men (7.7 ± 4) was below the Turkish cut-off. Mean Hospital Anxiety and Depression Scale-depression score of women was (8.2 ± 2.9) above the Turkish cut-off level of 7. The mean Hospital Anxiety and Depression Scale-depression scores of men were (6.2 ± 2.7) below the Turkish cut-off level. Females had significantly higher levels of depression and anxiety compared to men (P = .008 and P = .004; respectively). The highest anxiety and depression levels were observed in breast cancer patients and the lowest levels were in head and neck cancer patients. Conclusion: Cancer and coronavirus disease-2019 pandemic are serious public health problems. Many patients perceive cancer as the main lifethreatening disease. However, the pandemic increases the risk of depression and may affect cancer prognosis. Thus, psychological support for patients with cancer is advised during treatment, especially during the pandemic. Cite this article as: Dağdelen M, Demir E, Ergen A, et al. Evaluation of anxiety and depression scores in patients receiving radiotherapy during first wave of COVID-19 pandemic. Cerrahpaşa Med J. 2022;46(2):164-167.